Pelaksanaan peraturan daerah Kabupaten Bantul nomor 5 tahun 2016 tentang pamong desa khususnya mengenai pemilihan seleksi pamong desa di Kabupaten Bantul - Ike Kustini Rahayu; Francisca Romana Harjiyatni; T Diana Ethika (Universitas Janabadra, 2019)
This study aims to know the implementation of Regional Regulation Number 5 of 2016 concerning Village Official in the village official selection organization and factors that cause the lawsuit to Yogyakarta State Administration Court. This study used normative juridical approach through descriptive qualitative study. The study used primary data that was obtained through observation and interview and secondary data that was collected through books review and documents like constitution and others that related to this study. The data was then analyzed qualitatively. The result reveals that the implementation of Regional Regulation of Bantul Regency Number 5 of 2016 concerning Village Official does not resemble the original regulation. It can be seen that the society or the official does not fully understand every article of the regulation and that can lead to misperception. The misperception of the regulation directs to incorrect implementation. This is what is considered as fatal mistakes by the society so that this can be used as a basis for filling a lawsuit to the State Administration Court.